Phytochemicals and biological activities of explant and callus extracts of Lippia nodiflora (L.) Michx. / Dalilah Abu Bakar - Dalilah , Abu Bakar (2018)
The present study reports a protocol for efficient in vitro callus induction of Lippia nodiflora (L.) Michx. which belongs to Verbenaceae family, was found to possess natural product source that contains anticancer properties including remarkable bioactivity depends on its bioactive compounds and found to have flavonoids, sugar, steroids, essential oil, resins, tannins and other medicinally valuable constituents. Callus induction and shoot regeneration were achieved through culturing leaf and stem explants after disinfected with 70% ethanol for 3 minutes, 0.10% mercury chloride for 3 minutes and 20% sodium hypochlorite for 2 minutes on Murashige and Skoog (MS) medium (pH5.8) supplemented with single or combinations of auxins and cytokinins, which are naphthaleneacetic acid (NAA), 2,4-dichlorophenoxyacetic acid (2,4-D), indole-3-acetic acid (IAA), indole-3-butyric acid (IBA) and benzyladenine (BA), kinetin (KN). The highest shoot regeneration response was observed from MS medium without plant growth regulators (90%) while shoot regeneration from MS media supplemented with combination of IAA and BA which gave the highest multiple shoots with three shoots per explant. Maximum (92.50%) callus response was obtained on single plant growth regulators (PGRs) which was 2.50 mg/L NAA (118.60 mg/L) with light green friable callus, 90.00% response from 1.00 mg/L BA (42.70 mg/L) with green compact callus and 89.20% response from combination of 3.00 mg/L NAA: 2.00 mg/L KN (165.00 mg/L) with green compact and friable callus and 2.50 mg/L IBA: 1.00 mg/L BA (139.60 mg/L) with green compact callus. PGRs were evaluated for their influence on callus induction with biomass parameters in regular interval for in vitro callus growth curves which were plotted. Maximum biomass of the callus achieved on the third week. The callus was extracted with methanol using soxhlet apparatus and screening for stigmasterol and β-sitosterol was run using TLC, GC-MS, HPLC and HPTLC. Traces of steroids was found on TLC, while HPTLC exhibited clear bands of steroids on the Rf value of 0.46 minute. HPLC confirms the presence of stigmasterol at RT 8.69 and 8.71 minutes of standard stigmasterol and extracts, respectively. GC-MS analysis of the methanolic extract of L. nodiflora showed 15 peaks in total and the highest component in leaf extracts, octadecanoic acid with 93% and docosanoic acid with 80% in stem extracts. The extracts were tested on Escherichia coli, Bacillus subtilis, Aspergillus niger and Candida albicans for antimicrobial assay and DPPH radical scavenging activity was used for antioxidant evaluation. The methanolic extracts of in vivo leaf and stem explants with in vitro callus showed prominent antifungal activity against A. niger and C. albicans. The 50% (IC50) inhibition concentration of leaf, stem and callus extracts on the free radical scavenging DPPH were determined as 8231, 3959 and 16534 μg/ml respectively, showing there are high antioxidant activity on stem of L. nodiflora with 92.2% of scavenging activity. The inhibition of colon cancer cells production on HCT116 was successful with strong level of cytotoxity against cancer cells where dried leaf extracts gave the highest inhibition (4.19 μg/mL). Hence, Lippia nodiflora can be suggested to have a high potential to assist in the medical and pharmaceutical industry, especially on anticancer to aid successful cure for cancer.